Broadband Tracking of Characteristic Modes - Jianbin Zhu; Weiwen Li; Liangcai Zhang, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Effective mode sorting is the key to achieving characteristic mode (CM) analysis for open conductors. However, mode ordering just according to the eigenvalue magnitude may cause the mode crossing in the operating band. Mode tracking must be performed to obtain the correct mode ordering. Currently, mode tracking based on eigenvector correlation is usually only applicable to narrowband cases due to the large interval between the sampling frequency point and the first frequency. In this paper, the correlation calculation is directly performed between two adjacent frequencies, and the first frequency is not used as the anchor point. Due to the improvement of the eigenvector correlation, the broadband mode tracking is realized. Some numerical examples are used to verify the effectiveness of this algorithm.